New loci of Lychnophora ericoides and transferability to Lychnophora pinaster, endangered medicinal species from Brazil - Vieira, M. A. R. [UNESP]; Marques, M. O. M.; Haber, L. L.; Vigna, B. B. Z.; Bajay, M. M.; Pinheiro, J. B.; Souza, A. P.; Semir, J.; Zucchi, M. I. (Funpec-editora, 2014)
Lychnophora ericoides and Lychnophora pinaster are species used in popular medicine as analgesic or anti-inflammatory agents to treat contusions, rheumatism, and insect bites. In this study, 21 simple sequence repeat loci of L. ericoides were developed and transferred to L. pinaster. Three populations of L. ericoides and 2 populations of L. pinaster were evaluated; they were collected in the State of Minas Gerais. Population parameters were estimated, and the mean values of observed and expected heterozygosity were 0.297 and 0.408 (L. ericoides) and 0.228 and 0.310 (L. pinaster), respectively. Greater genetic variability was observed within populations than between populations of L. ericoides (62 and 37%) and L. pinaster (97 and 2.8%). These results provide information for genetic conservation and taxonomic studies of these endangered species.
Keywords: Microsatellite; Population genetics; Arnica; Medicinal plant